![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
{(x+2y)²-(x+y)(x-y)-5y²}/2x,其中x=-2,y=2分之1
展开全部
先化简
{(x+2y)²-(x+y)(x-y)-5y²}/2x
={x^2+4xy+4y^2-x^2+y^2-5y²}/2x
=4xy/2x
=2y
其中x=-2,y=2分之1
则原式=2*1/2=1
祝学习进步
{(x+2y)²-(x+y)(x-y)-5y²}/2x
={x^2+4xy+4y^2-x^2+y^2-5y²}/2x
=4xy/2x
=2y
其中x=-2,y=2分之1
则原式=2*1/2=1
祝学习进步
展开全部
原式=(x²+4xy+4y²-x²+y²-5y²)//2x
=4xy/2x
=2y
=2×1/2
=1
=4xy/2x
=2y
=2×1/2
=1
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
-4
解:原式=[x2+2xy+2xy+4y2-(x2-y2)-5y2]/2x
=(x2+4xy+4y2-x2+y2-5y2)
=4xy/2x (1)
把x=-2,y=1/2代入(1)式,得-4
解:原式=[x2+2xy+2xy+4y2-(x2-y2)-5y2]/2x
=(x2+4xy+4y2-x2+y2-5y2)
=4xy/2x (1)
把x=-2,y=1/2代入(1)式,得-4
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询